Epithelial membrane antigen-reactive feline chordoid meningioma in a European wildcat (Felis silvestris). (February 2023) - Franzen, Jan; Soto, Sara; Meier, Daniela; Rüttener, Michael; Oevermann, Anna
Abstract: Meningioma is the most frequent intracranial neoplasm in cats. Here we describe the first case of chordoid meningioma (CM), a rare grade II meningioma subtype, in a 5.5-year-old European wildcat ( Felis silvestris ) from a Swiss zoo. The wildcat was found dead after a clinical history of neurological signs and clinical suspicion of a carcinoma in the right external ear canal with concurrent chronic otitis. Post-mortem examination revealed a large intracranial, extra-axial and intradural neoplasm that invaded into the right ear canal and had histological features compatible with CM, which has been only reported in humans and dogs. Neoplastic cells expressed vimentin but were negative for glial fibrillary acidic protein, S100 and pancytokeratin. Immunohistochemistry revealed epithelial membrane antigen (EMA) expression in neoplastic cells. To the best of our knowledge, we provide the first evidence of EMA expression in feline meningioma.